2005
DOI: 10.1002/ird.152
|View full text |Cite
|
Sign up to set email alerts
|

Understanding water delivery performance in a large-scale irrigation system in Peru

Abstract: During a two-year field study the performance of the water delivery was evaluated in a large-scale irrigation system on the north coast of Peru. Flow measurements were carried out along the main canals, along two secondary canals, and in two tertiary blocks in the Chancay-Lambayeque irrigation system. The most important finding was the unexpectedly high accomplishment rate of the actual delivery at field level compared with the on-request schedule. Delivery performance ratios (DPRs) were very close to unity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…One of the main contributors in this particular field is Horst (1996Horst ( , 1998, who discusses the need to simplify irrigation infrastructure as many systems would require too complicated management arrangements. One could question whether this relation is really that direct; Vos (2005), Van der Zaag (1992), Hunt and Hunt (1976) and Hunt (1988) suggest that higher complexity (and larger scale) of infrastructure does not necessarily complicate irrigation management or require central authority. Furthermore, within his basically qualitative analysis, Horst focuses on division structures and leaves out canal behaviour altogether.…”
Section: Research On Irrigation Managementmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the main contributors in this particular field is Horst (1996Horst ( , 1998, who discusses the need to simplify irrigation infrastructure as many systems would require too complicated management arrangements. One could question whether this relation is really that direct; Vos (2005), Van der Zaag (1992), Hunt and Hunt (1976) and Hunt (1988) suggest that higher complexity (and larger scale) of infrastructure does not necessarily complicate irrigation management or require central authority. Furthermore, within his basically qualitative analysis, Horst focuses on division structures and leaves out canal behaviour altogether.…”
Section: Research On Irrigation Managementmentioning
confidence: 94%
“…If used, downstream control is adopted for main canals; lower canals remain under upstream control. Whichever is the situation, in many schemes with a central upstream water distribution system, volumetric delivery could be introduced or is already applied in practice (see Vos, 2005). However, in many cases introducing some kind of demand-based delivery would require a shift in the traditional task of any central authority: instead of sending water according to schedule, it has to make sure that all the demands of the farmers in the irrigation scheme can be met as effectively as possible.…”
Section: Modernizationmentioning
confidence: 98%
“…The results also indicate that this irrigation scheme can provide good service to farmers. Some studies have shown that a flexible water delivery system and good water delivery service capacity are important ways to improve water use efficiency and promote modernization of irrigation schemes [21][22][23]. In recent years, the Chinese government has made efforts to promote the modernization of irrigation schemes.…”
Section: Performance Of Water Allocation and Water Deliverymentioning
confidence: 99%
“…In Peru this this situation could disrupt the water cycle in the glacierdependent basins, affecting water regulation and availability (Servicio Nacional The Tinajones hydrological system is basically a run-off-river system with a relative small off-river storage reservoir, where both structures function complementarily (Vos, 2005).…”
Section: Chancay-lambayeque Irrigation District (Clid) Lambayeque Perumentioning
confidence: 99%
“…Seventy percent of this land operates with permanent licenses and 30 percent with permits. The system is basically a run-off-river system with a relative small off-river storage reservoir (Vos, 2005). Thus, the role of the Tinajones Reservoir is primarily to store water from the Chancay River's surplus during the wet season, which will be reallocated in the valley for irrigation during drier months, July to September.…”
Section: Appendix J Institutional Framework For the Management Of Sumentioning
confidence: 99%